Изучение плазмонных резонансов металлического нанопровода с двойным слоем (концентрической нанооболочки) - Шпилькин, А. Р.; Стогний, Н. П. (ХНУРЕ, 2021)
Typical problem of electrodynamics that based on effective analyticalnumerical investigation of stationary fields in systems of two-dimensional structure has been solved. Isolated metal nanowire with double shell were studied. All the possible plasmons of configuration of «nanomatryoshka» (or concentric nanoshell) has been described and classified. Corresponding equations for determining the complex eigenvalues has been obtained. Field distributions in the near-field, their frequency and quality factor (Q) has been considered.
Keywords: Плазмонный резонанс; нанопровод; нанооболочка